PENINGKATAN PRODUKTIFITAS PENGUSAHA MIKRO TAHU SUKUN MALANG - Maria, Evi; Kadarusman, Kadarusman; Irawati, Rina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
Abstract: In addition to being known as the city of Malang chips tempe and fruit chips, also known as tofu which is commonly referred to by the community as